Employee Performance: Extrinsic Motivation, Transformational Leadership, Innovation Climate Moderation Incentives - Dharmanto, Agus; Wahyu Setyawati, Novita; Sri Woelandari, Dewi (International Journal of Psychology and Health Science, 2023)
The purpose of this research is to prove to provide views through the findings of scientific articles related to the variables in this study. This research methodology uses a qualitative approach and examines the variables of this study. One type or method of scientific writing is a form of literature research. Theoretical analysis, analysis of relationships between variables, books, and journals, online and offline, obtained from Mendeley, Google Scholar, and other online media. Peer-reviewed journals are listed in the Journal Metrics Table below, the findings of scientific articles in literary studies with the results that there is an influence between There is Influence of Incentives with Employee Performance, There is an Influence of Innovational Climate with Employee Performance, There is an Influence of Intrinsic Motivation with Employee Performance and There is a Transformational Influence of Leadership with Employee Performance, it is evident from research by strengthening and providing views for future research and also the existence of gap variables or differentiators that can be used in future research listed in this scientific article. The recommendation from the results of this study is that there are findings from literature studies of dozens of scientific articles with differentiating variables that can be used in future research by other researchers.